1985
DOI: 10.1002/jsfa.2740361119
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis of petitgrain Eureka lemon essential oil by fused silica capillary column gas chromatography mass spectrometry

Abstract: The identification of Algerian petitgrain Eureka lemon essential oil was carried out by gas liquid chromatography-mass spectrometry in electronic impact mode using a fused silica capillary column (FFAP). The results enabled a previous study on this oil to be completed where the relative retention data and chemical derivation reactions had been performed. A preparative gas chromatography was applied to give a better g.c.-m.s.analysis of minor compounds; thus, two new products (citronellyl n-propionate and cedro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Among these factors we can include environment, soil fertility, the content of beneficial microorganisms, the state of immaturity (green color), and unpeeled vs. peeled fruit juice [14][15][16][17]. Additionally, the volatile fraction may be altered by analytical method, sampling, and equipment used [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors we can include environment, soil fertility, the content of beneficial microorganisms, the state of immaturity (green color), and unpeeled vs. peeled fruit juice [14][15][16][17]. Additionally, the volatile fraction may be altered by analytical method, sampling, and equipment used [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Volatile compounds in Meyer lemon (Moshonas et al, 1972), Italian lemon (Allegrone et al, 2006) and petitgrain Eureka lemon essential oil (Baaliouamer et al, 1985) have been reported, except Eureka lemon. Many studies showed the common volatile compounds in lemon.…”
Section: Introductionmentioning
confidence: 99%
“…d-Limonene plays a potential role in preventing breast cancer (Miller et al, 2011), and the antioxidant activity of lemon essential oils has been confirmed (Di et al, 2010). Lemon products are also important for food industry and health care (González-Molina et al, 2010).Volatile compounds in Meyer lemon (Moshonas et al, 1972), Italian lemon (Allegrone et al, 2006) and petitgrain Eureka lemon essential oil (Baaliouamer et al, 1985) have been reported, except Eureka lemon. Many studies showed the common volatile compounds in lemon.…”
mentioning
confidence: 99%